Análise dos impactos causados pela interferência antrópica em população de Araucaria angustifolia - Bortoncello, Vanessa Lando (2018)
The Ombrophilous Mixed Forest is home of a great diversity of wildlife and plant species which form interactive and differentiated communities, such as Araucaria angustifolia (Bertol.) Kuntze. The seeds after-ripening of this species interferes with the forest dynamics, constituting an important food resource. Despite its ecological, historical and socioeconomic importance, the forest was replaced by crops, pastures and cities, and currently it is difficult to find remnants which represent the primary characteristics of this phytophysiognomy. These anthropogenic impacts may interfere with vegetation physiognomy within the same forest formation, radically changing the environment. In this study, an area of High Montane Mixed Ombrophilous Forest was sampled, located at Reserva Particular do Patrimônio Natural -de-Altitude (SC), an area which presents a history of anthropic impacts, such as selective logging, pig raising and cattle grazing. To understand the effect of these interferences on Araucaria angustifolia (Bertol.) Kuntze population structure, the area was sampled between January and November 2017 with the aim to: (1) evaluating how the anthropic action over the last years may contribute to forest conservation and araucaria regeneration, (2) investigate the amount of A. angustifolia seeds which reaches the forest soil, being available to wildlife, as well as estimating seed productivity per hectare. The quantitative study for the first objective was conducted using plots sampling, which were randomly distributed within the forest. 90 subplots were sampled, totalizing 3.6 ha. The population structure was considered by the individuals’ distribution in five different demographic categories, being measured 5,244 individuals, approximately 1457 ind.ha. It was also noticed the existence of a critical phase for the species development. To sample the seed rain, 90 seed collectors were installed, totalizing 90 m² of the total sampled area. The seeds were removed from the collectors between June 2017 and May 2018. In total, 1804 seeds (12,38 kg) were collected, since, 217 showed signs of wildlife predation, which is quite diversified, as verified in the pattern of marks left in the seeds peel. In order to reinforce the pine nut productivity data, were sampled 30 female of Araucaria reproductive individuals. Both methods used provided similar results. In the seed collectors method, the results show a total of 1.876.62 kg/ha, while in the estimated productivity method a total of 1,463 kg / ha was obtained. This study provides a current record of the study area, demonstrating that the historical process of anthropic impacts promoted a positive effect on the Araucaria population, considering the regeneration and seedling density.The estimated and sampled productivity is high at RPPN Papagaios-de-altitude, suggesting its strong potential for regeneration and species attraction which interact with araucaria, reaching its goal of conserving biological diversity.